A luminescência do Eu3+ para elucidação estrutural: Apropriação e utilização de conceitos e linguagens por estudantes de iniciação científica - Silva, Rodrigo Regis Campos da (2010)
In this work, we have carried out a review about how the luminescence of Eu3+ is used for structural elucidation, more specifically, analysis of the emission spectra of this ion furnishes information about its chemical environment. We also have accomplished a survey with some undergraduate students by application of a semi-structured questionnaire, to assess the way in which these pupils take ownership of certain concepts involving luminescence, especially that of Eu3+. It was noted that the scientific initiation stage generally provides learners with the language that enables them to debate on various concepts related to the luminescence of Eu3+ and its use for structural elucidation. However, from some students’ answers it was possible to note a mechanical appropriation of concepts, without concern about understanding. There seems to be a difference between making science and understanding science. This is worrisome because making science, in general, is one of the main objectives of the research laboratories where undergraduate students work, but it is not necessarily possible to make them understand the concepts they use in this setting.